Structural Basis for the 14-3-3 Protein-Dependent Inhibition of Phosducin Function - Kacirova, Miroslava; Novacek, Jiri; Man, Petr; Obsilova, Veronika; Obsil, Tomas (Biophysical journal, 2017)
Phosducin (Pdc) is a conserved phosphoprotein that, when unphosphorylated, binds with high affinity to the complex of βγ-subunits of G protein transducin (Gtβγ). The ability of Pdc to bind to Gtβγ is inhibited through its phosphorylation at S54 and S73 within the N-terminal domain (Pdc-ND) followed by association with the scaffolding protein 14-3-3. However, the molecular basis for the 14-3-3-dependent inhibition of Pdc binding to Gtβγ is unclear. By using small-angle x-ray scattering, high-resolution NMR spectroscopy, and limited proteolysis coupled with mass spectrometry, we show that phosphorylated Pdc and 14-3-3 form a complex in which the Pdc-ND region 45-80, which forms a part of Pdc's Gtβγ binding surface and contains both phosphorylation sites, is restrained within the central channel of the 14-3-3 dimer, with both 14-3-3 binding motifs simultaneously participating in protein association. The N-terminal part of Pdc-ND is likely located outside the central channel of the 14-3-3 dimer, but Pdc residues 20-30, which are also involved in Gtβγ binding, are positioned close to the surface of the 14-3-3 dimer. The C-terminal domain of Pdc is located outside the central channel and its structure is unaffected by the complex formation. These results indicate that the 14-3-3 protein-mediated inhibition of Pdc binding to Gtβγ is based on steric occlusion of Pdc's Gtβγ binding surface.
Keywords: Phosphorylation; fosfoproteiny; Protein Structure, Secondary; Proteolysis; vztahy mezi strukturou a aktivitou; fosforylace; Structure-Activity Relationship; Protein Binding; krysa rodu Rattus; GTP-Binding Protein Regulators; proteinové domény; sekundární struktura proteinů; zvířata; proteiny vázající GTP - regulátory; proteiny 14-3-3; proteolýza; protonová magnetická rezonanční spektroskopie; 14-3-3 Proteins; difrakce rentgenového záření; oční proteiny; X-Ray Diffraction; Eye Proteins; vazba proteinů; Protein Domains; Scattering, Small Angle; Rats; maloúhlový rozptyl; Animals; Proton Magnetic Resonance Spectroscopy; Phosphoproteins